Assessment of harvest and post-harvest losses of major pulses in India - R K Vishwakarma; S N Jha; Anil K Dixit; Amanpreet Kaur; Anil Rai; Tauqueer Ahmed (Agricultural Economics Research Review, 2023)
A concurrent, national-level survey covering 14 agro-climatic zones (ACZ) was conducted in 2012-14 to quantitatively assess the harvest and post-harvest losses in pulses. The loss, estimated at INR 38.77 billion, was due mainly to inappropriate harvesting and poor post-harvest management—the use of improper threshers, delayed harvesting, and improper storage practices. To reduce the losses, harvesting and threshing practices should be standardized and machines refined and proper storage infrastructure provided; and farmers, traders, and processors need to be trained in scientific storage practices.